Assessing Indonesia’s Leadership in the Advancement of ASEAN Political-Security Community under President Joko Widodo - Gibran Mahesa Drajat (President University, 2018)
This paper aims to examine Indonesia’s leadership in ASEAN as the regional organization advances its community building in areas of political-security. Indonesia, the largest state in Southeast Asia both from geographic and economic size, is known for its de facto leadership within the regional integration process of ASEAN. Such integration is mostly prominent in areas of multilateral engagement, conflict management, and democracy as well as human rights promotion. With President Joko Widodo at the helm of Indonesia’s presidency since October 2014, Indonesia has reoriented its foreign policy cornerstone on ASEAN into other channels that best serve its national interest. As Indonesia repositions its focus from ASEAN, there is a need to evaluate whether the trajectory of ASEAN Political-Security Community will continue to thrive under the consensual decision-making process among its ten member states known as ASEAN way. To evaluate Indonesia’s leadership in the advancement of ASEAN Political-Security Community under President Joko Widodo, the paper will review Indonesia’s initiatives to ASEAN and how they contribute towards Southeast Asia’s regionalism. Subsequently, three areas of Indonesia’s leadership in ASEAN Political-Security Community building will be examined: the maintenance of ASEAN Centrality, South China Sea dispute management, and promotion of democracy and human rights. The paper concludes that ASEAN way works not only when ASEAN member states find a common ground on regional issues that affect their respective domestic politics. A presence of informal and voluntary leadership where “matured” member states bring about initiative and persuasion is needed to maintain ASEAN’s strategic relevance in Asia-Pacific. For this reason, Indonesia’s legitimacy as an informal leader in ASEAN plays an important role to ensure that the organization remain united and central to its member states.Keywords: ASEAN Political-Security Community, Indonesian Foreign Policy, Regional Leadership